PENGARUH KURS RUPIAH, INFLASI DAN SUKU BUNGA TERHADAP EKSPOR UDANG INDONESIA - Sitorus, Christian Desmon; Purba, Martin Luter; Purba, Elvis F (Jurnal KAFEBIS, 2023)
This study analyzes the influence of exchange rates, inflation, and interest rates on shrimp exports in Indonesia from 1999 to 2019 using multiple linear regression. The research findings indicate that the exchange rate and inflation positively influence shrimp exports, whereas the interest rate negatively impacts them. The regression coefficient for the exchange rate is 10.015, which indicates that each depreciation of the rupiah by 1 rupiah per year will increase shrimp exports by 10.015 tons per year. Conversely, the interest rate has a negative regression coefficient of -3519.690, suggesting that each 1% increase in interest rates will reduce shrimp exports by 3.519,690 tons per year. Inflation has a positive regression coefficient of 3.333,168, indicating that each 1% increase in inflation will increase shrimp exports by 3.333,168 tons per year. However, only the exchange rate shows a significant relationship, with inflation and interest rates not significantly impacting shrimp exports. The model's coefficient of determination is 58.3%, meaning that approximately 58.3% of the variation in shrimp exports can be explained by the exchange rate, inflation, and interest rates. This study provides crucial insights for policy makers and the shrimp industry in considering the factors affecting shrimp exports for the creation of applicable policies and strategies.